2011
DOI: 10.1111/j.1420-9101.2011.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of distribution and prevalence of avian malaria in blue tit populations across Europe: separating host and parasite effects

Abstract: Although avian malarial parasites are globally distributed, the factors that affect the geographical distribution and local prevalence of different parasite lineages across host populations or species are still poorly understood. Based on the intense screening of avian malarial parasites in nine European blue tit populations, we studied whether distribution ranges as well as local adaptation, host specialization and phylogenetic relationships can determine the observed prevalences within populations. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 51 publications
6
54
1
Order By: Relevance
“…In contrast to our study, the authors detected much lower lineage diversity (only three lineages: pTUR-DUS1, hPARUS1, pBT7). In the set of samples collected in 1994, Merilä and Andersson (1999) reported a much lower general prevalence of parasites (27 % in 259 individuals) than in Szöll} osi et al (2011) and in the current study, and domination of parasites from genus Haemoproteus (84 % of infections). The discrepancy between the current and previous studies may be associated with the pattern of sampling (several breeding seasons vs. a single breeding season) and differences in the sample size (n M&A = 259; n Sz = 41; n here = 762).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to our study, the authors detected much lower lineage diversity (only three lineages: pTUR-DUS1, hPARUS1, pBT7). In the set of samples collected in 1994, Merilä and Andersson (1999) reported a much lower general prevalence of parasites (27 % in 259 individuals) than in Szöll} osi et al (2011) and in the current study, and domination of parasites from genus Haemoproteus (84 % of infections). The discrepancy between the current and previous studies may be associated with the pattern of sampling (several breeding seasons vs. a single breeding season) and differences in the sample size (n M&A = 259; n Sz = 41; n here = 762).…”
Section: Discussionmentioning
confidence: 96%
“…All interactions were considered but discarded from the final model if non-significant Significant terms (p \ 0.05) are shown in bold Andersson (1999). In the set of samples collected in , Szöll} osi et al (2011 reported the general prevalence of 87.9 % with the majority of infections caused by Plasmodium (75 %). In contrast to our study, the authors detected much lower lineage diversity (only three lineages: pTUR-DUS1, hPARUS1, pBT7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this region differs from other habitats where studies on avian malaria have been conducted so far. It is known that different habitats with differing levels of ecological interactions and environmental changes may provide different compositions influencing the dynamics of the parasite-vector-host triad (Shutler et al 1996;Garvin and Remsen 1997;Piersma 1997;Mendes et al 2005;Durrant et al 2006;Arriero and Moller 2008;Belo et al 2011;Szöllözi et al 2011;Delgado-v and French 2012;Loiseau et al 2012). An interesting point raised by our results is the proposal that transmission of hemosporidians occurs in loco.…”
Section: Discussionmentioning
confidence: 99%
“…Since most molecular studies of hemosporidian parasites have examined genetic diversity at the cyt b locus only (e.g., Belo et al 2011;Marzal et al 2011;Svensson-Coelho and Ricklefs 2011;Szöllősi et al 2011), sequences in public databases are almost exclusively cyt b haplotypes, and thus a global phylogeographic context, needed for the estimation of the number of colonizations and dating analyses, cannot be provided for other markers. Analyses of the genetic diversity of hemosporidian parasites increasingly suggest that species described on the basis of morphological characters are actually species complexes (e.g., Sehgal et al 2006).…”
Section: Haplotype Identification and Diversitymentioning
confidence: 99%